Hierarchical Optimization Method for Ship Navigation in Multiple Emission Control Areas - Ruihao, Sun; Moduo, Yu; Wentao, Huang; Xinsheng, Zhang; Heng, Song (2022 IEEE Sustainable Power and Energy Conference (iSPEC), 2022)
While the marine transportation industry is responsible for most global transportation tasks, it also accounts for a large proportion of greenhouse emissions. With the goal of carbon neutrality, emission control and marine carbon trading scheme are developed. Transportation ships will be subject to the emission control area with multiple protection levels. In this paper, a hierarchical optimization method of ship integrated power system (IPS) is proposed to reduce transportation costs by splitting the optimization problem via different time scales. Then, the operation problems of the ship's powertrain and power system are solved, respectively. The cost of the proposed method and the traditional constant navigation schemes are compared. The results show that the proposed method can reduce the total cost of the route by adjusting the speed flexibly according to different protection levels in each control area.